Sistem Monitoring Pengiriman Alat Kerja Dengan Mengunakan Teknologi CouchDB - Achmad Noe’man; M. Hadi Prayitno (Journal of Informatic and Information Security, 2020)
CV. BJS is a company engaged in the rental of work tools, especially heavy equipment, and serves in the areas of Java, Sumatra, Kalimantan, Sulawesi and Bali. The Work Tools will be sent using company vehicles. The problem that arises from the delivery process is the unknown presence of delivery vehicles from both the company and the customer side, so customers often complain because there is no certainty about the arrival of the heavy equipment being rented. In this study, 2 applications have been made that can answer company problems. The first application, also known as administrative application, is made for administrative processes that are web-based and will be accessed by internal companies and customers. The second application, an Android-based application used by heavy equipment deliverers, will inform the whereabouts of the vehicle through CouchDB technology which is also used to provide real-time tracking and monitoring of the system.